Economic Fundamentalism and its Dangers - Gylys, Povilas (Ekonomika, 2002)
Explicit or (and) implicit ideologies, theories or conceptions are behind our visions, strategies, programmes and consequently actions. They serve as a cognitive frameworks and guidelines for majority of our endeavours.Part of such theoretical frameworks suffer from fundamentalistic perception of reality, which is based on reduction of objects and spheres of reality to some parts, sides or elements. Economy alongside religion and politics is one of the sphere where fundamentalism is often present. Soviet fundamentalism and market fundamentalism arc the most vivid examples of economic fundamentalism of modem times.Soviet fundamentalism was based on false reductionistic assumption that private entreprenership, market mechanism represent negative, even evil side of economic reality and that progressive and effective trends and forces are expressed exceptionally through sociality. Coercive collectivism and suppression of the market forces was both the theory and policy in the Soviet system. Soviet doctrine required to squeeze out market forces from official economy. Therefore these forces usually had to reappear on the “shadow”, informal side of economic life. Finally, Soviet system collapsed. The fundamentalistic, reductionistic, unrealistic character of it’s doctrine is the basic explanation of the demise of the system.In the process of transformation dominating economic doctrine in Lithuania as in the most Central and Eastern European countries became neoliberalism, which, in our view, represents another, opposite extreme - market fundamentalism. The heavy emphasis on individualism, believe in omnipotence and infallibility of market and treating sociality as an exogenous, external to economy are expressions of simplistic reductionism and thus fundamentalism.In modem economy the role of sociality is important. This importance is increasing by growing demand for public goods. Being by their nature non-rivalry, non-market goods they play substancial role in the sustainable economic development not only locally, but globally as well. Therefore, market fundamentalism, which is unwilling or unable to admit the role of local and global public goods as products of sociality, if pursued as an official policy could hamper the normal economic development and could lead us to a blind alley.